Is there an advocate in the house? The role of health care professionals in patient advocacy. Issue 1 (1st February 2002) - Schwartz, L
Abstract : It remains unclear what patient advocacy actually entails and what values it ought to embody. It will be useful to ascertain whether advocacy means supporting any decision the patient makes, or if the advocate can claim to represent the patient by asserting well-intentioned paternalistic claims on the patient's behalf. This is especially significant because the position of advocate brings with it certain privileges on the basis of of presumed insight into patient-perceived interests, namely, entitlement to take part in clinical decision making and increased professional standing. Three issues related to patient advocacy will be explored: are patient advocates necessary; what does advocacy entail, and who ought to represent patients in this way—arguments for and against prospective candidates will also be covered. The paper considers whether advocates are necessary since not only can they be dangerously paternalistic, but the salutary values advocacy embodies are already part of good professional health care.